2012
DOI: 10.3917/eh.065.0083
|View full text |Cite
|
Sign up to set email alerts
|

Early years in University development in management education: reflections and reminiscences on the University of Birmingham (1950s-1970s)

Abstract: Résumé Cet article est fondé, en partie, sur les souvenirs personnels d’un acteur qui a été témoin des premiers développements de l’enseignement de la gestion dans les universités britanniques entre les années 1950 et 1970. En particulier, ce récit résulte de son expérience au sein de l’Université de Birmingham et du paradoxe suivant : bien que Birmingham ait été une université pionnière dans l’enseignement de la gestion, elle n’a pas fondé une des premières business schools britanniques des années 1960, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Further details about the history of organization and management studies at Birmingham can be found inMinkes (2011).AU5…”
mentioning
confidence: 99%
“…Further details about the history of organization and management studies at Birmingham can be found inMinkes (2011).AU5…”
mentioning
confidence: 99%